Reversibilidade das alterações motoras e da tirosina hidroxilase em um modelo progressivo de parkinsonismo em ratos - Abritta, Roberta Teixeira Rocha (2020)
Parkinson's disease (PD) is a chronic and progressive neurodegenerative disease,characterized by progressive loss of dopaminergic neurons, mainly in the substantia nigraparscompacta (SNpc). Studies employing animal models have sought to mimic the progressivenature of behavioral and pathophysiology features of PD, each one with advantagesanddisadvantages. Reserpine (RES) model, which mimics the progressive nature of PD, isbasedon repeated administration of 10 to 15 injections with a low dose (0.1 mg.kg-1) inrats.However, the interruption of the RES administration is accompanied by a recoveryoftheobserved changes. The present study aimed to verify whether the prolonged treatment withRES allows to mimic the progressive and irreversible nature of PD. Thirty-two maleWistarrats were used, divided into 4 groups: Control (CTR); Reserpine (RES); Control andsubsequent abstinence period (CTR.A); RES and subsequent abstinence period (RES.A). Allanimals received 45 subcutaneous injection of RES (0.1 mg.kg -1) or vehicle, one every48h.On day 90, animals from CTL and RES groups were killed by transcardiac perfusionandthebrains were submitted to immunohistochemical analysis of tyrosine hydroxylase(TH).Animals in groups CTR.A and RES.A remained in the experimental protocol for another30days, but without receiving injections. Throughout the experiment the animals were subjectedto catalepsy tests and evaluation of oral movements to assess motor activity. Animals treatedwith RES showed progressive motor alteration in the catalepsy test fromday36andprogressive alterations, from day 20, in the evaluation of oral movements, inthethreeparameters observed: 1- oral tremor, 2- tongue protrusion and 3-chewing. Reserpine-treatedrats showed reversibility of motor changes (catalepsy and oral movements) 30daysaftertreatment interruption. The evaluation of TH immunoreactivity showed the treatment withRES was able to induce a reduction in the number of neurons in the SNpc andVentralTegmental Area (VTA), besides reduction in the relative optical density in the dorsal striatum(ED). The RES.A group showed recovery of TH immunoreactivity only in VTA. The45injections of RES, despite showing reversible motor changes, induced irreversible damageinthe nigrostriatal pathway. In conclusion, the results found showed that, after 45 injectionsofRES, the animals showed reversible motor changes, however they induced an irreversibledamage in nigrostriatal pathway during the evaluation period.